2002
DOI: 10.1098/rspb.2001.1904
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for habitat partitioning based on adaptation to environmental light in a pair of sympatric lizard species

Abstract: Terrestrial habitats exhibit a variety of light environments. If species exhibit evolutionary adaptations of their visual system or signals to habitat light conditions, then these conditions can directly influence the structure of communities. We evaluated habitat light characteristics and visual-signal design in a pair of sympatric species of lizards: Anolis cooki and Anolis cristatellus. We found that each species occupies a distinct microhabitat with respect to light intensity and spectral quality. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 33 publications
2
134
0
Order By: Relevance
“…If displaying in any or all of these contexts incurs fitness costs through, for example, increased likelihood of predation, then dewlap size might possibly be constrained by receiver-independent costs, regardless of the cost of bite force expression. Indeed, studies of visual signalling in particular suggest that dewlaps play an important role in general anole ecology in contexts besides sexual selection [72,73]. Furthermore, Irschick et al [47] showed that individual male dewlaps decrease in size in both the field and the laboratory following the cessation of major breeding activity in a New Orleans A. carolinensis population, suggesting that there may indeed be some cost to bearing large dewlaps.…”
Section: Discussionmentioning
confidence: 99%
“…If displaying in any or all of these contexts incurs fitness costs through, for example, increased likelihood of predation, then dewlap size might possibly be constrained by receiver-independent costs, regardless of the cost of bite force expression. Indeed, studies of visual signalling in particular suggest that dewlaps play an important role in general anole ecology in contexts besides sexual selection [72,73]. Furthermore, Irschick et al [47] showed that individual male dewlaps decrease in size in both the field and the laboratory following the cessation of major breeding activity in a New Orleans A. carolinensis population, suggesting that there may indeed be some cost to bearing large dewlaps.…”
Section: Discussionmentioning
confidence: 99%
“…How animals minimize the effects of environmental degradation on signal propagation is a classic focus of communication research (1)(2)(3) and is often central to understanding the way animals communicate (4)(5)(6) and interact with each other (7)(8)(9). Signal detection theory (10) and empirical studies (3) show that simple signal components suffer lower rates of environmental attenuation than more complex, information-rich components.…”
mentioning
confidence: 99%
“…Percent displaying is the percentage of time a lizard was dewlapping, head bobbing, or performing some other social display behavior. Data for A. barbatus are taken from Leal and Losos (2000); these data were collected for both males and females, including some subadults, and do not include information on moves per minute.…”
Section: Behavioral Observationsmentioning
confidence: 99%
“…The literature on resource partitioning in tropical lizard communities suggests that the use of different perch sites and microhabitats with different irradiance and thermal properties often allows sympatric species to avoid intense interspecific competition (Schoener and Gorman, 1968;Schoener, 1977;Heatwole, 1982;Williams, 1983;Jenssen et al, 1988;Hertz, 1991;Losos, 1992;Powell et al, 1996;Leal and Fleishman, 2002). Martínez Reyes (1995) found 11 anole species at Soroa and noted that most of them perched on tree trunks or shrubs.…”
Section: Introductionmentioning
confidence: 99%